2016
DOI: 10.1002/jssc.201600342
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell SiO2‐coated Fe3O4 with a surface molecularly imprinted polymer coating of folic acid and its applicable magnetic solid‐phase extraction prior to determination of folates in tomatoes

Abstract: A novel core-shell magnetic surface molecularly imprinted polymer with folic acid as a template was successfully synthesized by the sol-gel method. To generate Lewis acid sites in the silica matrix for the interaction of the metal coordinate with the template, 3-aminopropyltriethoxysilane was used as a functional monomer, tetraethyl orthosilicate as a cross-linker, and aluminum ions as a dopant. The magnetite encapsulated by the silica shell plays an important role as a magnetic-coated polymer. The synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In recent years, molecular imprinting solid‐phase extraction has been extensively used to efficiently separate trace compounds from complex matrixes . For example, molecular imprinting solid‐phase extraction was used to extract thiabendazole from citrus , folates from tomatoes , bovine hemoglobin from the bovine blood , and GA from natural resources . Hu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, molecular imprinting solid‐phase extraction has been extensively used to efficiently separate trace compounds from complex matrixes . For example, molecular imprinting solid‐phase extraction was used to extract thiabendazole from citrus , folates from tomatoes , bovine hemoglobin from the bovine blood , and GA from natural resources . Hu et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular imprinting solid-phase extraction has been extensively used to efficiently separate trace compounds from complex matrixes [18][19][20][21]. For example, molecular imprinting solidphase extraction was used to extract thiabendazole from citrus [22], folates from tomatoes [23], bovine hemoglobin from the bovine blood [24], and GA from natural resources [25][26][27]. Hu et al prepared MIPs on magnetic mesoporous silica for the selective extraction and determination of GA from grape, apple, peach, and orange juices [25].…”
mentioning
confidence: 99%
“…All mixtures were prepared using a mixture of ACN/toluene (75/25, v/v) as porogen up to a final volume of 25 mL and subjected to thermal polymerization at 60 • C for 24 h. Once polymerization was complete, it was observed that polymerization did not occur for mixtures containing a 1:1 MAA/HEMA ratio (MMIP3 and NMIP3). It has been reported that the presence of hydrophilic monomers leads to polymers with insufficient rigidity [16]. In this regard, likely the large amount of HEMA used for the preparation of MMIP3 and NMIP3 did even prevent the polymerization process and consequently, such mixtures were discarded for further experiments.…”
Section: Polymerization Mixturementioning
confidence: 99%
“…It is clear that the incorporation of an MIP layer to magnetic nanoparticles presents significant advantages in sample preparation, taking into account the extraction efficiency provided by the surface modified magnetic nanoparticles and the extraction selectivity provided by MIPs [9,10]. At this regard, several works have reported the preparation of molecularly imprinted core-shell magnetic nanoparticles (MMIPs) to be used in magnetic dSPE and have been employed for the extraction of pesticides [11][12][13], triazophos [14], aflatoxins [15], and folates [16], among others. Analytes are selectively separated from the correspond-ing organic extract of different kind of samples although the application to water-based samples is rather scarce due to poor recognition abilities of MIPs in aqueous samples.…”
Section: Introductionmentioning
confidence: 99%
“…Attributing to the specific synthetic method, MIPs own a specific memory function and possess the performances of high selectivity and recognition ability to the target compounds . In recent years, MIPs have been widely used as separation media in SPE and SPME . They are also used in the fields of chromatographic separation , chemical sensor etc.…”
Section: Introductionmentioning
confidence: 99%